Digitalization of Bulgarian Cultural Heritage - Georgiev, Georgi Nikolov (Journal of Economic Development, Environment and People, 2019)
The research of historical heritage is related to creation, storage and distribution of visual information about them. With the development of digital technologies, the three-dimensional scanning and visual regeneration of buildings of cultural heritage combined with 3D virtual reconstruction is becoming increasingly important tool for understanding and reconstructing the past. Instead of expensive laser scanning, cheaper photogrammetric methods for creating and processing of spatial (3D) images of historical and architectural monuments are finding a growing application. The article analyses the opportunities for use of different ICT tools, including inexpensive digital imaging options for preservation and exhibiting of large and diverse Bulgarian cultural heritage.